Comparison of Stunting Clusters For Each Province in Indonesia in 2019 and 2020 With 2021 and 2022 Using the K-Means Method - Daniel Tunggono Saputro (Jurnal Indonesia Sosial Teknologi, 2024)
Stunting is a condition in the development of toddlers due to malnutrition characterized by a height below average, and the consequence if a toddler is affected by stunting is that it hurts the child's cognitive development and causes generative diseases in adulthood. Presidential Decree No. 72 of 2021 concerning the acceleration of reducing stunting is a form of the government's seriousness in dealing with stunted toddlers. This research uses the K-Means algorithm method, which calculates data using RapidMiner software, looking for differences in the number of stunting data cluster members in 2019-2020 and 2021-2022. There are changes in provincial data in each cluster after comparison. The high cluster, initially three provinces, became nine, and the low cluster, initially 10, became 7. The average percentage of each high cluster in 2019-2020 compared to 2021-2022 experienced a decrease of 9.264%, and for the medium cluster, it experienced a decrease of 5.13%, and for the low cluster, there was a decrease of 3.736%.